Case study of the integration of electronic patient‐reported outcomes as standard of care in a head and neck oncology practice: Obstacles and opportunities. Issue 3 (27th October 2020) - Strachna, Olga; Cohen, Marc A.; Allison, Monica M.; Pfister, David G.; Lee, Nancy Y.; Wong, Richard J.; McBride, Sean M.; Mohammed, Raia R.; Kemeny, Elizabeth; Polubriaginof, Fernanda C. G.; Kassa, Alyse; Hannon, Michael; et al.
Abstract : Background: Patient‐reported outcomes (PROs) allow for the direct measurement of functional and psychosocial effects related to treatment. However, technological barriers, survey fatigue, and clinician adoption have hindered the meaningful integration of PROs into clinical care. The objective of the authors was to develop an electronic PROs (ePROs) program that meets a range of clinical needs across a head and neck multidisciplinary disease management team. Methods: The authors developed the ePROs module using literature review and stakeholder input in collaboration with health informatics. They designed an ePROs platform that was integrated as the standard of care for personalized survey delivery by diagnosis across the disease management team. Tableau software was used to create dashboards for data visualization and monitoring at the clinical enterprise, disease subsite, and patient levels. All patients who were treated for head and neck cancer were eligible for ePROs assessment as part of the standard of care. A descriptive analysis of ePROs program implementation is presented herein. Results: The Head and Neck Service at Memorial Sloan Kettering Cancer Center has integrated ePROs into clinical care. Surveys are delivered via the patient portal at the time of diagnosis and longitudinally through care. From August 1, 2018, to February 1, 2020, a total of 4154 patients completed ePROs surveys. The average patient participation rate was 69%, with a median time for completion of 5 minutes. Conclusions: Integration of the head and neck ePROs program as part of clinical care is feasible and could be used to assess value and counsel patients in the future. Continued qualitative assessments of stakeholders and workflow will refine content and enhance the health informatics platform. Lay Summary: Patients with head and neck cancer experience significant changes in their quality of life after treatment. Measuring and integrating patient‐reported outcomes as a part of clinical care have been challenging given the multimodal treatment options, vast subsites, and unique domains affected. The authors present a case study of the successful integration of electronic patient‐reported outcomes into a high‐volume head and neck cancer practice. Abstract : Integration of an electronic patient‐reported outcomes (ePROs) program into a head and neck oncology practice is feasible and will allow for the measurement of outcomes. This program can be used as a model for the future development of ePROs programs across oncology practices.